AB0699 EFFECT OF SWITCHING BETWEEN TUMOR NECROSIS FACTOR INHIBITOR IN SPONDYLOARTHRITIS. (June 2019) - abla, hedia ben; Rekik, Sonia; Boussaid, Soumaya; Jammali, Samia; Sahli, Hela; Cheour, Elhem; Elleuch, Mohamed
Abstract : Background: The introduction of new drugs, in particular tumour necrosis factor inhibitor (TNFi) has revolutionized the treatment of spondyloarthritis (SpA). Meanwhile, about 30% of patients do not react to first-line TNFi. To date, there is no recommendations available forthe treatment of SpA patients after first TNFi failure. Objectives: In this study we assessed the effectiveness of a second and third biotherapy in patients with SpA with an inadequate response to previous TNFi and to analyze the survival of the second biotherapy Methods: This study included patients with SpA who had had at least two biotherapies. Treatment response was noted at 3 months. At 6 months, we assessed the maintaining of effectiveness in Spa. We studied the elements of a good response to the second biotherapy. Results: Our population of study included 30 SpA. During the second treatment, response rate was achieved by 80% after 3 months. No difference was noted between first and second TNFi among switchers. 86, 7%maintained response at twelve months. For axial forms, decrease in BASDAI was significant at 3 months. For peripheral forms, an improvement of the swollen and tender joint counts was observed and was significant at 3 months. Four patients have received a third TNFi. Response rate was achieved by all of them after 3 months. All of them maintained response at 6 months.The elements of a good response founded were;the early age of the SpA starting(<30y.o), the high value of initial CRP, the use of ESSG criteria, the SpA type, the extra articular signs, the first biotherapy and the reponse at 3 months to it, the drugs taken when second biotherapy were initiated a low initial EVA and BASFI. Conclusion: These real-life data show that, after discontinuation of a first TNFi, switching to a second biotherapy in SpA is related to significantly improving of clinical effectiveness compared to a first TNFi. References: none Disclosure of interests: None declared